Exploration: Safe and clean mining on Earth and asteroids. (1st June 2020) - Dong, Longjun; Sun, Daoyuan; Shu, Weiwei; Li, Xibing
Abstract: The shallow mineral resources tend to run out in the near future. Meanwhile, numerous catastrophic safety accidents have been induced and serious environmental damage has been caused due to the long-term predatory mining. In this paper, we explored the safe and clean mining on Earth and asteroids by integrating safety and cleanliness into the whole process of mining production. As for the safe and clean mining on Earth, we elaborated the root causes and major influencing factors for the safety accidents occurred frequently and presented specific measures to optimize the entire mining production in the aspects of open-pit mining and underground mining. On the other hand, the possible mining methods and facilities on asteroids were proposed through the overall consideration of safety and cleanliness, which mainly include the asteroid capturing method, open cutting method, and underground filling method. Furthermore, the adaptations of these off-Earth mining methods to different types of asteroids, as well as their own advantages and disadvantages were discussed and clarified. Additionally, some helpful suggestions were discussed to prevent and control the current disasters caused by traditional mining methods. The exploration of safe and clean mining on Earth and asteroids can not only provide guidance for the current and future extraction of valuable mineral resources, but also a benefit for the sustainable development of green mining and environment. Highlights: Safety and cleanliness are integrated into the whole process of mining production. Entire mining production on Earth is optimized from different aspects. Three mining methods and relevant facilities for mining asteroids are explored. Suggestions for preventing current mining-induced accidents on Earth are presented. Adaptations, merits, and defects of proposed off-Earth mining methods are clarified.